Perancangan Net Support School Sebagai Monitoring Praktikum pada Laboratorium Komputer SMP Negeri 2 Bukittinggi - Muhammad Tafsir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research was conducted on the importance of computer laboratories and the implementation of teaching and learning activities because most of the material is practical. It will be very difficult to carry out practical learning without learning tools or media that are in accordance with the guidance of the curriculum material, there are other subjects that cannot be done without a laboratory. The practicum learning process is less than optimal because one of the reasons is that students don't pay too much attention to the learning material. And there are no tools or software to monitor student work in the process of using computers. The Network Development Lifecycle method is used to develop and design network topologies, in this case the use of the Net Support School application to monitor learning in the laboratory at SMP Negeri 2 Bukittinggi. The result of implementing net support school is that teachers can share learning materials from the computer server. Teachers can also supervise and control students' activities in using computers while the learning process is in progress. So using the net support school application is very helpful for use in the learning process.